Hybrid Solar Spectral‐Splitting Photovoltaic‐Thermal Hydrogen Production Systems - Yu Tian; Pooria Hadikhani; Nada Alati; Bryce S. Richards; Gan Huang (Advanced Science, 2025)
Abstract Utilizing solar energy to produce green hydrogen is sustainable, but achieving high efficiencies remains challenging. In this study, a hybrid solar spectral‐splitting photovoltaic‐thermal hydrogen (SSPVTH) system is developed. Leveraging emerging membrane‐less electrolyzers, this system simultaneously employs photovoltaics and solar thermal energy to maximize solar‐to‐hydrogen (STH) production efficiency. The SSPVTH system based on gallium arsenide solar cells achieves an STH efficiency of 21.1%, representing a 31.1% relative improvement over a conventional PV‐electrolyzer that relies solely on photovoltaic electricity for water electrolysis. When equipped with perovskite photovoltaics, the system attains an STH efficiency of up to 19.0%. Additionally, with the integration of direct current power converters, the system maintains relatively stable performance across varying solar irradiance levels. Overall, this study provides a new design with the potential for achieving high‐efficiency hydrogen production through hybrid solar technologies.